Entrepreneurial Orientation and International Performance: The Moderating Effect of Decision-Making Rationality - Deligianni, Ioanna; Dimitratos, Pavlos; Petrou, Andreas; Aharoni, Yair (My University, 2016)
This research examines how entrepreneurial orientation (EO) influences international performance (IP) of the firm taking into account the moderating effect of decision-making rationality (DR) on the EO-IP association. Such an investigation is significant because it considers the interplay of strategic decision-making processes supported by the bounded rationality concept in the entrepreneurship field. Drawing from a study on activities of 216 firms in the United States and United Kingdom, the evidence suggests that DR positively moderates the EO-IP association. The findings suggest that managers can improve IP by combining EO with rational (analytical) processes in their strategic decisions.
Keywords: Export performance; Business research; Firm performance; Strategic orientation; Market; Model; Fit; Organization